Cutaneous coccidiomycosis presenting with a facial plaque - Watson, Ian T. (Proc (Bayl Univ Med Cent), 2019)
We present the case of a 55-year-old black man with coccidiomycosis presenting as a cutaneous plaque on the upper lip. Coccidiomycosis, or “valley fever,” is caused by the virulent, dimorphic, soil-dwelling fungus Coccidiodes immitis. Seen in up to 50% of symptomatic patients, skin involvement by coccidiomycosis can present as papules, pustules, plaques, nodules, abscesses, or ulcerations. Diagnosis of coccidiomycosis relies on serology and identification in clinical specimens, and first-line treatment includes fluconazole, ketoconazole, or itraconazole. Recognizing the cutaneous manifestations of this mycotic infection is essential for diagnosis in otherwise asymptomatic patients.